The Generalization of some Problems in Calculus of Variations into the Space of Analytic Functions - Skaf, Hanaa (Latakia University Journal -Basic Sciences Series, 2018)
This paper deals with the following conditional extremal problem: Find the minimum value of the integral functional under some boundary conditions and additional constraints of type , where is some function defined in Banach Space of holomorphic functions in unit disc and is a regular curve in this disc. It have been shown that the solution of the above problem satisfies the system of differential equations Where and are the Lagrange Multipliers. Some applications and additional examples are given.